Kinerja Keuangan Berbasis Konsep BSC (Balance Scorecard) Berdasarkan Prespektif Financial - Helencia, Kiki; Agustian, Efandri (TIN: Terapan Informatika Nusantara, 2023)
The purpose of this research is to understand how the Balanced Scorecard is implemented as an alternative performance measurement for companies using a qualitative descriptive approach. Data analysis based on the Balanced Scorecard concept serves as a guide for researchers to elaborate on information at Bank 9 Jambi, indicating performance measurement based on three perspectives: financial perspective, customer perspective, and internal business perspective. The results of this research provide information on the performance measurement of Bank 9 Jambi using the Balanced Scorecard method for the period 2017-2019. Researchers can draw conclusions regarding the performance measurement of the company using the Balanced Scorecard method at PT. Bank 9 Jambi, considering the financial perspective of PT. Bank 9 Jambi appears to be good. From the customer perspective, the performance of PT. Bank 9 Jambi seems satisfactory. The internal business process perspective suggests that continuous development is needed for PT. Bank 9 Jambi.